2020
DOI: 10.1128/iai.00237-20
|View full text |Cite
|
Sign up to set email alerts
|

Scnn1b -Transgenic BALB/c Mice as a Model of Pseudomonas aeruginosa Infections of the Cystic Fibrosis Lung

Abstract: The opportunistic pathogen Pseudomonas aeruginosa is responsible for much of the morbidity and mortality associated with cystic fibrosis (CF), a condition that predisposes patients to chronic lung infections. P. aeruginosa lung infections are difficult to treat because P. aeruginosa adapts to the CF lung, can develop multidrug resistance, and can form biofilms. Despite the clinical significance of P. aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The Tg+ mice are susceptible to spontaneous bacterial infection, a likely outcome of airway mucus obstruction, which is cleared significantly within four weeks of age ( 26 , 31 ). Based on a previous report that demonstrated a beneficial effect of HMGB1 inhibition on bacterial clearance in CFTR -/- mice ( 21 ), we anticipated that airway epithelial cell-specific HMGB1-deficient Tg+ mice will have a better bacterial clearance compared to HMGB1-sufficent Tg+ mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tg+ mice are susceptible to spontaneous bacterial infection, a likely outcome of airway mucus obstruction, which is cleared significantly within four weeks of age ( 26 , 31 ). Based on a previous report that demonstrated a beneficial effect of HMGB1 inhibition on bacterial clearance in CFTR -/- mice ( 21 ), we anticipated that airway epithelial cell-specific HMGB1-deficient Tg+ mice will have a better bacterial clearance compared to HMGB1-sufficent Tg+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the Tg+ mice exhibit various features of mucoobstructive airway diseases including mucus obstruction, mucous cell metaplasia, lung inflammation, and bacterial infection (2,(25)(26)(27)(28)(29)(30). The Tg+ neonates are prone to early spontaneous bacterial infections that are cleared almost completely by the adulthood (26,31). HMGB1 levels are elevated in the BALF of Tg+ mice (18).…”
Section: Introductionmentioning
confidence: 99%
“…These mice overexpress the β subunit of the epithelial sodium channel (β-ENaC) in the airway epithelium, resulting in increased sodium absorption similar to CF. In both studies these β-ENaC mice cleared the infections more slowly than the WT mice, indicating impaired clearance ( Mall et al, 2004 ; Brao et al, 2020 ). One of the studies further investigated the effect of PAO1 and non-mucoid or mucoid CF clinical isolates in cytokine responses and histological features ( Brao et al, 2020 ).…”
Section: Cystic Fibrosis Lung Diseasementioning
confidence: 94%
“…Multiple delivery methods exist for administering P. aeruginosa into the lungs of animals, and the chosen delivery technique is important as it determines the accuracy and precision of dosing, progression of infection, and has impacts on the animal’s health and welfare. Inoculation techniques include adding bacteria to the drinking water ( Coleman et al, 2003 ), intranasal application ( Schroeder et al, 2001 ; van Heeckeren et al, 2006 ; Brao et al, 2020 ), tracheostomy ( van Heeckeren et al, 2000 ; Hoffmann et al, 2005 ; Bayes et al, 2016 ) and non-surgical intratracheal delivery ( Schroeder et al, 2001 ; Munder et al, 2011 ) ( Table 1 ). Some factors that should be considered when deciding on which technique to use to deliver P. aeruginosa to the lungs include the target location and the number of bacteria to be delivered to that location, minimising contamination of non-target tissue, the reproducibility of the technique, and the physiological impact on the animal (e.g.…”
Section: Cystic Fibrosis Lung Diseasementioning
confidence: 99%
“…Studies of these mice (βENaC-Tg) demonstrated that increased airway sodium absorption causes airway surface liquid depletion, reduced mucus transport, and spontaneous CF-like lung disease with airway mucus obstruction, impaired mucociliary clearance, emphysema, and chronic inflammation including airway neutrophilia, similar to human CF lung disease [19,[21][22][23]. P. aeruginosa can infect the airways of βENaC-Tg mice, both in planktonic and biofilm forms, and form bacterial aggregates [23,24], a well-described feature of P. aeruginosa in CF patients with chronic infection [25][26][27][28]. The goal of this work was to characterize NETs and further details of the neutrophil-mediated inflammation in the airways of βENaC-Tg mice, as the best murine CF lung disease model, in the absence of bacterial infections.…”
Section: Introductionmentioning
confidence: 99%